Marginal accuracy of CAD / CAM all ceramic crowns as affected by different degrees of axial taper - Ahmed Esmat Elsherbieny; Carl Hany Halim; Jylan Fouad Elguindy (Cairo : Ahmed Esmat Elsherbieny, 2013)
The aim of this study was to investigate the effect of non surgical periodontal therapy on GCF level of visfatin in patients with moderate chronic periodontitis. The purpose of the present study was to assess the level of visfatin in samples of GCF from chronic periodontitis patients before and after scaling and root planing (SRP). The study included 30 patients divided into two groups: Group {u2160}: consisted 20 patients with chronic periodontitis treated by scaling and root planing. Group {u2161}: the control group which consisted of ten healthy individuals. Clinical parameters including gingival index, plaque index, pocket depth and clinical attachment level were measured and GCF samples were collected using paper points for each patient at baseline for both groups and 4 weeks after treatment by (SRP) for group {u2160} only. Visfatin detection in GCF was performed using a commercial ELISA kit. The results of the present study revealed that the highest levels of visfatin concentrations in GCF were obtained in chronic periodontitis group {u2160} and the least levels were found in the control group {u2161} with a statistically significant difference between them
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Prosthodontics
Issued also as CD
Keywords: Chronic periodontitis; Periodontitis; Visfatin